Prawie dla wszystkich, ale i prawie nikt skorzysta - Sioma, Radosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The paper presents the first monograph of the famous interwar weekly ‘Wiadomości Literackie’, whose first editor-in-chief was Mieczysław Grydzewski. As suggested by the subtitle, Małgorzata Szpakowska’s book "Wiadomości Literackie" has – almost for everyone – an ambition to be popular with the general public. An overriding principle of the book’s composition is that thematic and separate chapters have been devoted to, for example, reportages in ‘Wiadomości’, literary criticism, visual arts (and others), as well as the editor-in-chief, prewar anti-Semitism and the magazine’s recipients. Undoubtedly, Szpakowska’s monograph goes beyond being a thematic research paper. The authoress managed to present the historical development of the literary magazine and situate it against the background of political and social changes, from the first years after regaining of independence up to the last months before the outbreak of the Second World War. The book is an insightful study of a phenomenon important to Polish culture.
Almost for everyone, but almost no one will benefit from it
Keywords: „Wiadomości Literackie”; Grydzewski, Mieczysław; monografia; czasopismo; monograph; literary magazine